2020
DOI: 10.1044/2020_jslhr-20-00096
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics Associated With Stuttering Persistence: A Meta-Analysis

Abstract: Purpose The purpose of this meta-analytic study was to identify clinical characteristics, defined as child factors that can be assessed by a speech-language pathologist as part of a routine speech-language evaluation that may differentiate children who persist in stuttering from children who eventually recover from stuttering. Clinical characteristics explored included sex, age at onset, family history of stuttering, stuttering frequency and severity, speech-language skills, and temperament. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 89 publications
2
18
1
Order By: Relevance
“…Yairi and Ambrose (1999) confirmed that the frequency of typical disfluencies did not differentiate groups of CWS and children who do not stutter (CWNS). We and others also note that the frequency of typical disfluencies is statistically similar between groups of CWS-ePer and CWS-eRec (Singer et al, 2020;Walsh et al, 2020). On the other hand, stuttering-like disfluencies (SLDs)-sound prolongations, blocks, sound/syllable repetitions, and monosyllabic whole-word repetitions-not only differentiate CWS from those who do not stutter but also distinguish CWS-ePer and CWS-eRec (Walsh et al, 2020).…”
Section: Severity Of Stuttering-like Disfluenciessupporting
confidence: 61%
See 3 more Smart Citations
“…Yairi and Ambrose (1999) confirmed that the frequency of typical disfluencies did not differentiate groups of CWS and children who do not stutter (CWNS). We and others also note that the frequency of typical disfluencies is statistically similar between groups of CWS-ePer and CWS-eRec (Singer et al, 2020;Walsh et al, 2020). On the other hand, stuttering-like disfluencies (SLDs)-sound prolongations, blocks, sound/syllable repetitions, and monosyllabic whole-word repetitions-not only differentiate CWS from those who do not stutter but also distinguish CWS-ePer and CWS-eRec (Walsh et al, 2020).…”
Section: Severity Of Stuttering-like Disfluenciessupporting
confidence: 61%
“…This difference was also not statistically significant; the two groups largely overlapped (Walsh et al, 2020). The recent meta-analysis by Singer et al (2020) reported later ages at stuttering onset for children who would eventually persist.…”
Section: Epidemiological Factorsmentioning
confidence: 83%
See 2 more Smart Citations
“…Interviews with the child and caregivers• Observation of caregiver/child interaction • Observation of the child's speech in various speaking situations • Screening and testing, as needed, of the child's language, speech, temperament, hearing, and related abilities•Observation and testing of the child's speech fluency and stuttering behavior, reactions to stuttering, and impact of stuttering•Risk factor analysis (examining data from various aspects of the assessment to hypothesize about child's risk for continuing to stutter;Singer et al, 2020) Sample Data for Area 1: Stuttering-related background information• Caregivers' view of the problem in general and main concerns • Caregivers' report of concomitant concerns and other diagnoses • Caregivers' report about the development of stuttering, including family history of persistence and recovery, time since onset and developmental course, and other speech or language issues • Caregivers' perceptions of prior therapy for stuttering or other concerns • Caregivers' knowledge and experiences related to stuttering, including beliefs about causal, eliciting, and reinforcing factors for stuttering (e.g., Palin Parent Rating Scales [Palin PRS; Millard, & Davis, 2016) • Caregivers' goals for stuttering treatment (e.g., Solution-Focused Brief Therapy [SBFT] scaling; Nicholas, 2015) • Child's perceptions and current knowledge about stuttering • Child's readiness for change and goals for treatment (e.g., SBFT scaling) • Assessment and progress reports from prior treatment, if applicable Sample data for Area 2: Speech, language, temperament, and related background information • Caregiver's views about the child's development, including cognitive and social-emotional development, behavior, selfregulation abilities, perfectionistic tendencies, and coping skills • Clinician's observations of the child's communication and related skills • Scores on screenings and tests, as needed, of child's language development, speech sound production skills, and temperament (e.g., Child Behavior Checklist [CBCL; Achenbach & Rescorla, 2000], Child Behavior Questionnaire [CBQ; Rothbart et al, 2001]) • Scores on screenings and tests of related factors, including anxiety (e.g., Spence Children's Anxiety Scale; Spence, 1998), as appropriate Sample data for Area 3: Speech fluency and stuttering behavior • Caregivers' observations and perceptions of fluency and stuttering, including types of disfluencies, physical tension, secondary characteristics, and severity (e.g., Palin PRS, Severity Ratings [SR]; Yairi & Ambrose, 2005) • Caregivers' observations and perceptions of and factors that affect fluency and stuttering in various speaking situations • Child's perceptions and self-ratings of speech, fluency, and stuttering, including types of disfluencies, physical tension, secondary characteristics, and severity, in various speaking situations, as possible based on child's cognitive development • Clinician's data on speech, fluency, and stuttering (e.g., frequency/percent of syllables stuttered [%SS or words stuttered, %WS], type, duration, and severity [e.g., SEV; O'Brian et al, 2004] of disfluencies; physical tension; speaking rate; naturalness [Martin & Haroldson, 1992], other speech characteristics) in different situations • Scores on tests and measures of speech fluency and stuttering (e.g., Stuttering Severity Instrument [SSI; Riley, 2009], Test of Childhood Stuttering [TOCS; Gillam et al, 2009]) Sample data for Area 4: Child's reactions to stuttering • Caregivers' observations of child's affective, behavioral, and cognitive reactions to stuttering (e.g., embarrassment, anxiety, shame, fear, avoidance, word substitution) • Child's report of reactions to stuttering and coping responses • Scores on tests of child's reactions to stuttering and attitudes about communication (e.g., KiddyCAT; Vanryckeghem & Brutten, 2007) Sample data for Area 5: Reactions to stuttering within the environment • Caregivers' reac...…”
mentioning
confidence: 99%